7 YEARS OF DWELLING TIME POLICY - Ramadhany Nugroho; Erna Setijaningrum; Ikhwan Mustaqim (DIA: Jurnal Administrasi Publik, 2024)
This study aims to gather responses from stakeholders regarding the Dwelling Time policy that has been in place for seven years, hoping to find new evidence to reduce logistics costs. This study uses a qualitative approach with a Case Study approach by conducting interviews with stakeholders operating in the Tanjung Perak Port related to goods importation. As a result, this study is expected to formulate more concrete and effective recommendations for improving the loading and unloading processes at the port and reducing logistics costs, eventually supporting the improvement of Indonesia's economic growth. The study shows that implementing the Dwelling Time policy to reduce logistics costs does not provide the expected outcome. Instead, it results in higher logistics costs due to PLP. Thus, the government needs to evaluate future policies. Collaboration among related agencies, namely port operators and regulators, by not carrying out PLP if the YOR position does not reach 60-70% and the extended stay indicator is a maximum of 7 days is a solution the author can provide. The government is also expected to continually evaluate policies that have been implemented if they have been running for more than five years. With the discovery of new evidence related to Dwelling Time, the definition of the problem also changes, requiring new solutions or more adaptive policies related to these changes.